AVANÇO DA AGENDA NEOLIBERAL: confrontos e resistência na implantação das Organizações Sociais em Florianópolis-SC - Valdeci Reis (Universidade Federal do Maranhão, 2018)
This is a theoretical study, with documentary research and literature review. The objective was to report and analyze the conjuncture of the process and ap- proval of a Bill that authorizes implementation of Social Organizations (OSs) in the city of Florianópolis-SC. It sought to highlight the clashes and conﬂicts involving as actors the executive and legislative branches, the trade union mo- vement and various segments of society, as well as the resistance strategies put in place. This project represents a severe blow on the part of multilateral agencies against public service, in other words, it’s a neoliberal proposal that is at a more advanced stage in several municipalities in Brazil. The resistance movement established in Florianópolis deserves to be highlighted due to the strength of the mobilization and because of the intense dialogue that took place with all society.